(untitled) (CIPEEX, 2025)
The text discusses obstetric violence (OV), addressing its definition, causes, and consequences. Historically, childbirth was conducted by midwives at home, but the medicalization of childbirth disregarded women’s agency, transforming it into a hospital event. OV includes abusive practices by healthcare professionals, such as unnecessary interventions and disrespectful treatment, and is influenced by social, racial, and gender inequalities. This paper aims to investigate, through a literature review, the factors associated with and the forms of obstetric violence against women during childbirth. The research is a bibliographic review with a qualitative approach and explores the various forms of this violence and its associated factors, such as gender and racial inequalities, especially against Black women. The results show that OV manifests in various ways; examples of these violences include the performance of Kristeller maneuvers and the use of forceps, as well as the use of inappropriate language, insults, and humiliations directed at the birthing women, influenced by socioeconomic factors, age, and racial inequalities, with Black women being particularly vulnerable. Furthermore, it emphasizes the need to restructure the training of professionals to improve the quality of care and prevent obstetric violence. It is essential that they are trained to provide the quality healthcare that women need during pregnancy, childbirth, and the postpartum period. Given the above, there is a predominance of obstetric violence cases during pregnancy, with an emphasis on physical and verbal forms. Among the main factors contributing to such occurrences are socioeconomic factors and social class. Therefore, it is imperative to promote structural changes and implement more inclusive and fair health policies to ensure more just and respectful care for all pregnant women.